Spectroscopic and Theoretical Studies of Potential Anti-Inflammatory Polycyclic Aromatic Fluorophenyl Substituted Acyclic and Heterocyclic Analogues Synthesized from 4, 4′-Difluorophenylchalcone. (14th September 2021) - Sheena Mary, Y.; Shyma Mary, Y.; Thomas, Renjith; Resmi, K. S.; Narayana, B.; Samshuddin, S.; Sarojini, B. K.
Abstract: The first principle calculations were performed using the B3LYP/cc-pVDZ level to find the structural and geometrical parameters, vibrational wavenumbers and various molecular properties of three fluorophenyl derivatives, 3, 5-bis(4-fluorophenyl)isoxazole (BISFPI), 2, 3-dibromo-1, 3-bis(4-fluorophenyl)-prop-1-one (BFPH) and 4, 6-bis(4-fluorophenyl)-2-phenyl-1H-indazol-3(2H)-one (FPPIH). The experimental bands are compared with theoretical wavenumbers and assigned using potential energy distribution analysis. The VCD spectrum is produced by the ring stretching modes are efficient configuration markers. The first hyperpolarizabilities of BISFPI, BFPH and FPPIH are respectively, 10.25, 33.82 and 20.34 times that of urea and hence good objects for further studies in nonlinear optics. Molecular electrostatic potential maps can suggest the sites which are prone from attack of the electron loving and nucleophilic systems. NBO analysis gives the stability of molecules arising from hyper conjugative interactions. In the case of molecules under study, molar refractivity values are increasing in the order, FPPIH > BFPH > BISFPI and this is responsible for the binding nature of the molecular systems. The docked ligands form stable complexes with the receptor arylmalonate decarboxylase inhibitor and the docking studies suggest that these compounds can be developed as new anti-inflammatory drugs.